Preventive wound drainage reduces esophageal fistula or infection after endoscopic resection of giant submucosal tumors in the esophagus - Liao, Qiao Yun; Tang, Yi Meng; Zhan, Li Sha; Fan, Yao (Endoscopy International Open, 2025)
Submucosal tunneling endoscopic resection (STER) has emerged as an innovative approach for the treatment of giant submucosal tumors (SMTs) in the esophagus. However, complications such as esophageal fistula or submucosal infection remain a concern. This article explores how preventive wound drainage can play a significant role in reducing these complications.We devised an innovative and straightforward method for negative pressure drainage. This approach involves positioning the drainage device with metal clips before closing the esophageal mucosa wound. A retrospective analysis was conducted on 46 patients with giant SMTs who underwent the STER procedure, among whom 28 had drainage and 18 had no drainage. Patient characteristics, adverse events, and risk factors were comprehensively evaluated.In 46 patients, the transverse diameter of the tumor exceeded 5 cm. No significant difference was observed in age, gender, tumor size, surgical scope, or mucosal injury between the two groups studied (P > 0.05). Esophageal fistula or submucosal infection rates in the drainage group were lower than those in the no drainage group (2/28 vs 14/18, P < 0.05). Subgroup analyses revealed that multiple injuries in the esophageal mucosa combined with full-thickness resection of the esophageal muscle layer were the immediate causes of esophageal fistula or submucosal infection following STER surgery.In the context of STER for giant esophageal submucosal tumors with muscular layer full-thickness resection and mucosal injury, preventive drainage is an effective strategy for minimizing postoperative esophageal fistula and submucosal infection complications.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Benign strictures; Dilation, injection, stenting